Sejarah Singkat Psikologi Pendidikan - Kartika Susila Putri; Dia Ayu Khairani; Abdurrahim Abdurrahim; Fauziah Nasution (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
According to some experts, educational psychology is a sub-discipline, not psychology itself. They assume that educational psychology does not have its own theory, concept and method. Simply and practically educational psychology is a knowledge based on psychological research that provides a series of resources to help carry out the duties of a teacher in the teaching and learning process. The method used is literature review. However, from the results of the literature review, information is obtained that educational psychology is a branch of psychology whose breakdown and emphasis is more on the growth and development of children, both physically and mentally, which is very closely related to educational problems, especially affecting the process of learning success. Psychology is a combination of two different sciences, psychology is the knowledge of psychology studying individual behavior, finding out the character of one's development. While education is guidance given to children. So educational psychology is the study of the soul. Keywords: History, Psychology, Education